Characteristics and Outcomes of Patients With Valvular Cardiogenic Shock - Raunak M. Nair, MD; Sanchit Chawla, MD; Feras Alkhalaileh, MD; Bahaa Abdelghaffar, MD; Agam Bansal, MD; Andrew Higgins, MD; Ran Lee, MD; Penelope Rampersad, MD; Umesh.N. Khot, MD; Wael A. Jaber, MD; Grant W. Reed, MD; Paul C. Cremer, MD; et al. (JACC: Advances, 2024)
Background: The clinical characteristics and outcomes of patients who develop cardiogenic shock (CS) secondary to primary valvular dysfunction (valvular cardiogenic shock [VCS]) remain unclear. Objectives: The purpose of this study was to describe the cohort of patients with VCS and understand their outcomes compared to other forms of CS. Methods: All patients admitted to Cleveland Clinic cardiac intensive care unit between January 1, 2010, and December 31, 2021, with a diagnosis of CS were retrospectively identified. Characteristics and outcomes for shock patients with VCS were compared to those without VCS. Results: A total of 2,754 patients were admitted to our cardiac intensive care unit with CS, of which 442 (16%) had VCS. The median age of patients with VCS was higher than those with non-VCS (70 years vs 64 years, P < 0.001) and were more likely females (40.3% vs 32.1%, P = 0.001). VCS was predominantly due to native valve dysfunction as compared to prosthetic valve dysfunction (71% vs 29%, P < 0.001), with the aortic valve noted to be the most common valve affected. Patients with VCS had higher 1-year (44% vs 37%, P < 0.001) and 30-day all-cause mortality (28% vs 20%, P < 0.001) compared to those without VCS. When compared to percutaneous intervention and medical therapy alone, surgical intervention in VCS was associated with the best short- and long-term outcomes (P < 0.001). Conclusions: VCS is associated with poor short and long outcomes. Native valvular dysfunction and aortic valve involvement account for the majority of patients with VCS. Definitive surgical therapy and expanding the role of percutaneous therapies may be pivotal in improving clinical outcomes in this high-risk cohort.